Sequential action of Caenorhabditis elegans Rab GTPases regulates phagolysosome formation during apoptotic cell degradation - Guo, Pengfei (National Academy of Sciences, 2010)
Phagocytosis of apoptotic cells requires recognition of cell corpses followed by internalization and enclosure within plasma membrane-derived phagosomes. Phagosomes undergo maturation to generate phagolysosomes in which cell corpses are degraded; however, regulation of the maturation process is poorly understood. Here, we identified Rab GTPase 14, which regulates apoptotic cell degradation in Caenorhabditis elegans. rab-14 mutants accumulate many persistent cell corpses owing to defective cell corpse clearance. Loss of rab-14 function affects several steps of phagosome maturation including phagosomal acidification and phagolysosome formation. RAB-14 and UNC-108/RAB2 are recruited to phagosomes at a similar stage and function redundantly to regulate phagosome maturation. Three Rabs, RAB-14, UNC-108/RAB2, and RAB-7, act in sequential steps to control phagolysosome formation. RAB-14 and UNC-108 recruit lysosomes, whereas RAB-7 mediates fusion of lysosomes to phagosomes. Our data reveal the sequential action of Rab GTPases in regulating tethering, docking, and fusion of lysosomes to apoptotic cell-containing phagosomes.